A 2nd helping of chicken soup for the soul : 101 more stories to open the heart and rekindle the spirit - Canfield, Jack, 1944-; Hansen, Mark Victor (Deerfield Beach, Fla. : Health Communications, 1995)
A collection of life-affirming anecdotes on the experiences of love, parenting, death, dreams, and learning.
On love -- On parenting -- On death and dying -- A matter of attitude -- On learning and teaching -- Live your dream -- Overcoming obstacles -- Eclectic wisdom.
Adult
Keywords: Parables; Spiritual life -- Anecdotes; Parables; Spiritual life -- Anecdotes